Experimental and Numerical Analysis of a 10 MW Floating Offshore Wind Turbine in Regular Waves - Hyeonjeong Ahn; Hyunkyoung Shin (Energies, 2020)
Floating offshore wind turbines (FOWTs) experience fluctuations in their platforms, owing to the various wave and wind conditions. These fluctuations not only decrease the output of the wind power generation system, but also increase the fatigue load of the structure and various equipment mounted on it. Therefore, when designing FOWTs, efficient performance with respect to waves and other external conditions must be ensured. In this study, a model test was performed with a 10 MW floating offshore wind turbine. The model test was performed by scaling down a 10 MW FOWT model that was designed with reference to a 5 MW wind turbine and a semisubmersible platform by the National Renewable Energy Laboratory and the DeepCwind project. A scale ratio of 1:90 was used for the model test. The depth of the East Sea was considered as 144 m and, to match the water depth with the geometric similarity of mooring lines, mooring tables were installed. The load cases used in the model test are combined environmental conditions, which are combined uniform wind, regular waves and uniform current. Especially, Model tests with regular waves are especially necessary, because irregular waves are superpositions of regular waves with various periods. Therefore, this study aimed to understand the characteristics of the FOWTs caused by regular waves of various periods. Furthermore, in this model test, the effect of current was investigated using the current data of the East Sea. The results obtained through the model tests were the response amplitude operator (RAO) and the effective RAO for a six degrees-of-freedom motion. The results obtained from the model tests were compared with those obtained using the numerical simulation. The purpose of this paper is to predict the response of the entire system observed in model tests through simulation.